Efficient synthesis of novel N-substituted 2-carboxy-4-quinolones via lithium bis(trimethylsilyl)amide (LiHMDS)-induced in situ cyclocondensation reaction. Issue 19 (13th February 2017) - Hasan, Phool; Aneja, Babita; Masood, Mir M.; Ahmad, Md. Belal; Yadava, Umesh; Daniliuc, Constantin G.; Abid, Mohammad
Abstract : Efficient synthesis of N -aryl-2-carboxy-substituted 4-quinolones with broad substrate scope and high regioselectivity. Abstract : A different approach for the synthesis of N -substituted 2-carboxy-4-quinolones using direct reductive amination followed by LiHMDS-induced cyclocondensation has been developed. A range of analogues of the title compounds with broad substrate scope were obtained in moderate yields and good regioselectivity.